GENETIC POLYMORPHISMS OF CYP2C9 GENE AMONG VOLUNTARY DONORS FROM THE MACEDONIAN BONE MARROW DONOR REGISTRY AND ITS IMPLICATIONS ON THERAPEUTIC DOSAGE OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS - Ribarski, Ordanche; Efinska Mladenovska, Olivija; Stamatovska, Kristina; Kirijas, Meri (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2022)
The CYP2C9 gene is related to the metabolism of several non-steroidal anti-inflammatory drugs (NSAID). Presence of different allele polymorphisms is associated with lack of enzyme activity and can lead to therapeutic failure. The aim of our study was to provide data about the distribution of CYP2C9 alleles in voluntary donors from the Macedonian Bone Marrow Donor Registry (MBMDR) and to calculate the activation score (AS) of CYP2C9 enzyme. We analyzed samples of 25 voluntary bone marrow donors by multiplex real-time polymerase chain reaction (PCR) test for detection of CYP2C9*2 and *3 polymorphisms. The samples were analyzed with 7500 Real-Time PCR System with FAM, VIC, ROX and Cy5 filters. We identified 13 donors with *1*1 diplotype, 7 with *1*3 diplotype, 4 with *1*2 diplotype and 1 donor with *2*3 diplotype. According to the calculated AS, 13 out of 25 individuals (54%) had normal AS value of 2, which refers to normal metabolizers (NMs). Eleven donors (44%) had AS value of 1-1.5, which refers to intermediate metabolizers (IMs) and only one donor (4%) had AS value of 0.5 which refers to poor metabolizer (PM). Even though the number of donors in our study is small and the results need to be evaluated in a larger cohort, it shows that different genotypes in the CYP2C9 gene are present among donors from MBMR. It is important to have it in mind especially when using NSAIDs that can be bought over-the-counter.
Keywords: pharmacogenetics; CYP2C9; NSAIDs; Macedonian Bone Marrow Donor Registry